Available bleeding scoring systems poorly predict major bleeding in the acute phase of pulmonary embolism. (14th October 2021) - Mathonier, C; Badoz, M; Besutti, M; Schiele, F; Meneveau, N; Guillon, B; Chopard, R
Abstract: Background: Bleeding prediction scores may help to guide acute management of patients with pulmonary embolism (PE). However, existing scoring systems have not been validated for in-hospital assessment. We aimed to compare 6 available bleeding scores, in a real-life cohort for the prediction of major in-hospital bleeding. Methods: We recorded in-hospital characteristics of 2, 754 PE patients included in a prospective observational multicenter cohort study contributing 18, 028 person-days of follow-up. We assessed the VTE-BLEED, RIETE, ORBIT, HEMORRA2HAGES, ATRIA, and HAS-BLED scores at baseline. ISTH-defined bleeding events were independently adjudicated. The accuracy of the scores for the prediction of in-hospital bleeding was evaluated and compared. Results: We observed 82 first in-hospital major bleeding events (3.0% (95% CI, 2.4–3.7)). Overall, the predictive power of bleeding scores was poor, with a C index ranging from 0.57 to 0.69 (Figure 1). The RIETE score had the numerically highest model fit and best discriminatory capacity, but without reaching statistical significance versus the ORBIT, HEMORR 2 HAGES, and ATRIA scores. The VTE-BLEED and HAS-BLED scores had significantly lower C indices, integrated discrimination improvement, and net reclassification improvement compared to the four others. Conclusion: Currently available scoring systems have insufficient accuracy for the prediction of in-hospital major bleeding in patients with acute PE. The development of acute-PE-specific risk scores is needed to optimally target patients that warrant bleeding-prevention strategies. Funding Acknowledgement: Type of funding sources: None.